Cultivating Creativity: A Journey in the Fundamentals of Information Technology Infrastructure Course - Esquicha-Tejada, José; Cornejo-Paredes, Andrea; Cuya-Zevallos, Carla; Portilla-Vilca, Evelyn; Angulo-Osorio, Javier; Montesinos-Murillo, Angel; Sapaico-del-Castillo, Cesar (LACCEI, 2024)
In the constant search for effective pedagogical strategies aimed at the comprehensive development of skills in students and with the purpose of contributing to social development, teachers must implement innovative approaches for the development of critical thinking, creativity, entrepreneurship, and socially responsible behavior. This research uses a methodology centered on strengthening creativity for systems engineering students in the subject of Fundamentals of Information Technology Infrastructure. By applying a proprietary methodology based on Design Thinking and challenge-based learning to university students, it reveals that 95.6% of students were satisfied with how the subject was conducted, using development boards (Arduino, NodeMCU, and Raspberry Pi), emphasizing how to create their first creative project and collaborate in a team. Additionally, it is evident that students strengthened their soft skills, as they are motivated to participate in different multidisciplinary innovation and/or entrepreneurship contests